Study I: economic feasibility of hot processing beef carcasses - J. McCoy; P. Nason; D. Chung; Curtis L. Kastner; A. Lawrence; Michael E. Dikeman; Melvin C. Hunt; Donald H. Kropf (Kansas Agricultural Experiment Station Research Reports, 1980)
Nearly all steer and heifer beef carcasses processed in the United, States are chilled before cutting. However, recent meat science research has shown that carcasses can be processed, and quality of meat maintained, with little or no chilling. Processing as defined here involves cutting the carcasses into subprimal pieces, removing bones and excess fat, sealing the pieces in vacuum packages, and placing the packages in palletized boxes. It is already known that substantial economic saving can be obtained from reduced storage and transportation costs of boxed beef, but little work has been done on the economic feasibility of hot processing.
Keywords: Cattlemen' s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Hot processing beef carcasses